THE MEANING AND VALUE OF SPIRIT IN ARU ORAL LITERARY TEXTS: DERRIDA'S HERMENEUTICAL REVIEW - Tuflih, Muhammad Alfian (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2025)
Indonesia is a country rich in ethnic groups that contribute to cultural diversity, one of which is literature. Contextually, literature is a form of self-expression that uses language as its medium. Aru or Angngaru is a literary work originating from South Sulawesi, especially the Makassar tribe and its surroundings. Aru is a text that reflects the noble values ​​of a citizen or soldier to his leader. Hermeneutics is the understanding of meaning in written works, one of which is literature. Through this research, the author wants to examine the text of aru through Derrida's hermeneutic approach. The method used is a literature study presented descriptively regarding how to study the meaning of the text. From the research, it was found that the meaning in the text of aru or Angngaru contains values ​​and norms of society that must be possessed, in the form of a sense of responsibility in carrying out mandates and accepting all consequences, courage, submission and obedience to leaders, and voluntary service with full humility to leaders.